A legal analysis of parental child abduction in Malaysia after The Hague Convention on the civil aspects of international child abduction / Rohayati Hussin, Sarirah Che Rose and Nuraisyah Chua Abdullah - Hussin, Rohayati; Che Rose, Sarirah; Abdullah, Nuraisyah Chua (Research Management Institute, 2012)
Globalisation has exposed people to interact between nationalities of different states. Marriage of cross-nationality is not a new phenomenon and it becomes more common now. However, when such marriage fails, a losing parent in custody may be tempted to abduct their children to his or her own country. The removal of children by unlawful parent to another jurisdiction is not a new trend in Malaysia as it has gained greater importance following the highly exposed case involving Raja Bahrin and his children. The Hague Convention of October 25, 1980 on the Civil Aspects of International Child Abduction came into force on December 1, 1983. The Hague Convention aims to protect children from unlawful removal from their respective countries and to establish procedures to ensure the children’s prompt return to the State of their habitual residence, as well as to secure protection for rights of access for respective parents. Malaysia has not acceded to The Hague Convention, unlike 82 countries worldwide and as such the question arises as to the legal position of the respective parents in cases of parental child abduction. Therefore, this study will focus on the aims and objectives of The Hague Convention on the Civil Aspect of International Child Abduction. Besides, this study will seek to examine the practices and relevant provisions in Malaysia in dealing with the issue of parental child abduction. At the end of the discussion, a recommendation will be made whether Malaysia should accede to The Hague Convention and to suggest any best solutions to curb this issue.